Pemanfaatan Teknologi Informasi Dalam Pembelajaran Bahasa Arab - Mardianah Haris (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2021)
This paper discusses how technology can be used in the Arabic learning process. Various problems of learning Arabic in accordance with the contexts faced in various educational institutions, the teaching staff allows modification of methods in teaching and learning. This can be done with the development of technology that contains a lot of information that can be used to improve learning outcomes. The discussion on the application of technology in Arabic learning contains questions, namely what forms of technology can be used, whether technology can play a role in the alignment and sustainability of Arabic learning from elementary to upper secondary level, whether technology can make students more interested in learning the language. Arabic, whether technology can create realization and relevance to what students feel, whether technology can create more varied Arabic learning media which is still lacking, whether technology can improve the ability or competence of educators in teaching Arabic, whether technology is able to take advantage of the time allocation for learning Arabic, is technology able to create an Arabic-speaking environment.